2017
DOI: 10.1080/01443615.2016.1269227
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating oxidised low-density lipoprotein and antibodies to oxidised low-density lipoprotein in preeclampsia

Abstract: Enhanced oxidative stress is involved in the pathogenesis of endothelial dysfunction in preeclampsia (PE). Circulating oxidised LDL (oxLDL) and antibodies to oxLDL (Ab-oxLDL) have been found to be associated with atherosclerosis. The objectives of this study were to investigate the association of oxLDL and Ab-oxLDL with PE and to assess the association between oxLDL and Ab-oxLDL. The levels of oxLDL and Ab-oxLDL were measured by enzyme-linked immunoassay in 78 women with preeclampsia (PE group) and 78 women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This is in line with previous data assessing the effect of oxLDL on vascular function in rat, mouse and human arteries 2,14,23,31 , and confirms that the overexpression of LOX-1 in the LOX-1tg mice is functional. Aside from being a well-known ligand for LOX-1, oxLDL is also a circulating factor that is increased in complicated pregnancies, such as preeclampsia 15,16 . Our data confirm our hypothesis that specifically in conditions of increased LOX-1 expression oxLDL reduces endothelium-dependent vasodilation and may thus contribute to systemic vascular dysfunction that is observed in women with preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with previous data assessing the effect of oxLDL on vascular function in rat, mouse and human arteries 2,14,23,31 , and confirms that the overexpression of LOX-1 in the LOX-1tg mice is functional. Aside from being a well-known ligand for LOX-1, oxLDL is also a circulating factor that is increased in complicated pregnancies, such as preeclampsia 15,16 . Our data confirm our hypothesis that specifically in conditions of increased LOX-1 expression oxLDL reduces endothelium-dependent vasodilation and may thus contribute to systemic vascular dysfunction that is observed in women with preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pregnancy complications such as preeclampsia have also been associated with endothelial dysfunction and placental and vascular oxidative stress 14 . Some reports have shown that oxLDL levels are higher in women with preeclampsia and have been associated with an increased risk for developing preeclampsia 15,16 . Moreover, LOX-1 expression was shown to be increased in omental arteries from women with preeclampsia, as well as in aortas from pregnant rats with reduced perfusion pressure, suggesting a potential role for LOX-1 in complicated pregnancies 4,5 .…”
mentioning
confidence: 99%
“…Previous studies (8,9) have highlighted that the oxidation of low-density lipoprotein (LdL) leads to upregulation of the levels of inflammatory factors, including tumor necrosis factor-α and interleukin-6, in the body, and may decrease the cell invasive ability of trophoblasts and promote cell apoptosis, thereby resulting in abnormal development of placenta and the occurrence of PE. According to the National center for Biotechnology Information (NcBI) database, LdL receptor-related protein 6 (LRP6) is highly expressed in placental tissues.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 One mechanism suggested to affect the BBB includes increased levels of oxidized low-density lipoprotein (oxLDL) in women with preeclampsia. 40,41 Increased oxidative stress in the placental circulation during preeclampsia causes oxidative conversion of LDL to oxLDL. oxLDL initiates multiple pathways in both endothelial and vascular smooth muscle cells, mostly through binding to its receptor lectinlike oxLDL receptor (LOX-1).…”
Section: Pathophysiologymentioning
confidence: 99%